Impact of gold prices on stock exchange market: a case of Karachi stock exchange market of Pakistan - Khan, Muhammad Shaique; Aziz, Abdul; Herani, Gobind M. (International Journal of Accounting and Economics Studies, 2016)
The objective of the study is to examine the long-term relationship between gold prices and KSE-100 index of the Karachi stock market Pakistan. For the foreign and domestic capital investors, it is assumed that the gold is the safest heaven for making investment. On the other handstock markets are considered highly volatile. This study uses monthly data of two hundred forty eight months from October 1993 to May 2014. Time-series data of both variables Karachi Stock Exchange 100 index (KSE-100) and gold prices have been collected from the official website of Karachi stock market and Forex.com. To achieve the aims of the study, several econometric tests have been applied such as unit root test by using Augmented Dickey-Fuller test, Johnson Co-integration test and Vector Auto-regressive Model (VAR). This study finds that there is no long-run relationship between KSE 100 index and gold prices. It is concluded investors should not consider KSE 100 index and gold prices as close alternatives rather they should make their decisions on subjective knowledge by aligning them with empirical evidence. While making decisions about gold prices last month’s price must be taken into consideration because current gold price is significantly influenced by last month’s gold price. Whilst making decision regarding KSE 100 index last two months’ fluctuations taken into consideration.
Keywords: KSE-100 Index; Gold Prices; Economic Development; Capital Investment.